Removal of heavy metal by micellar solubilization followed by coagulation flocculation process: article - Ku Zaidi, Ku Nur Haifaa Zafiraa; Noor Ismail, Kamariah; Puasa, Siti Wahida (2019)
Contamination of wastewater with heavy metals has become a crucial issue to the environment. Recently, micellar enhanced ultrafiltration (MEUF) is a common method that is widely used for the elimination of metals ion using membrane but unfortunately, this method is unfavourable due to the membrane fouling problem. In this research, micellar sollubilization process followed by coagulation flocculation process was applied for the removal of cadmium ion from wastewater. Sodium lauryl sulfoacetate was utilized as plant based surfactant in micellar solubilization process while both of ferric chloride and polyacrylamide were used in coagulation flocculation process. The effect of pH and effect of surfactant concentration on the cadmium Cd2+ removal were studied to determine the efficiency of micellar solubilization process. Results obtained from this research study shows that the highest percentage removal for coagulation flocculation process was 99.76% while for the micellar solubilization was obtained at 99.78%. Both of these methods occurred at pH 11 for the best removal efficiency of Cd2+. It was observed that highest removal efficiency of Cd2+ was achieved at 99.78% at surfactant concentration of 250 ppm. The regression analysis via Excel Software shows that R2 and adjusted R2 obtained for micellar solubilization were 0.85 and 0.82 respectively while R2 and adjusted R2 obtained for coagulation flocculation were 0.76 and 0.40 respectively. Regression statistics and ANOVA analysis justified that the mathematical expression can be used to forecast the removal efficiency of Cd2+ from wastewater